Corn Irrigation with Reduced Well Capacity - Rocio Reyes Esteves (Kansas Agricultural Experiment Station Research Reports, 2024)
One major challenge for western Kansas irrigated corn producers is sustaining or enhancing yields under declining well capacities or limited water supplies. Irrigation systems in the Central Great Plains can no longer supply peak irrigation needs throughout the summer months. Producers should rely on soil water reserves to keep the crop from water stress. Irrigated crop production is essential for agriculture in Western Kansas. Corn is the most popular commodity crop grown under irrigation (around 50% of the irrigated acres). Nevertheless, with declining water levels in the Ogallala aquifer, optimal application of limited irrigation water and sustainability practices are necessary. This study evaluated how irrigation management can be used to improve productivity when well capacity is limited and insufficient to meet crop requirements fully. The objective of this study was to determine the grain yield response of corn to different irrigation capacities. Field studies were conducted at the Kansas State University Northwest Research and Extension Center near Colby, KS, during the 2023 growing season. The study was a factorial design of irrigation capacities (limited to 8, 9, and 10 inches per season and a dryland treatment) with a corn hybrid (DeKalb DKC62-69RIB) with excellent drought tolerance. Grain yields increased by using a drought-tolerant hybrid with a planting rate of 28,000 seeds/a. Average grain yields increased from 194.7 bu/a to 202.3 bu/a when irrigation capacity increased.
Keywords: corn; irrigation; linear irrigation; irrigation capacities; dryland